Eames Furniture Source Book - Kries, Mateo, 1974-; Kugler, Jolanthe, ....- (Weil am Rhein : Vitra Design Museum, 2017)
Through models, material studies, prototypes and production examples of the Eames estate held at the Vitra Design Museum, this publication aims to reconstruct the genesis of the most relevant furniture designs by Charles and Ray Eames and shed light on their influence on the development of new and innovative materials. New insights into the thought processes and work practices of this legendary couple are revealed, designers whose work was driven by philosophical ideals that privileged knowledge, discovery and discipline, and embraced the potential of technology and science for the common good. Among the most important American designers, Charles Eames (1907–78) and Ray Eames (1912–88) are celebrated for their groundbreaking work in furniture, architecture, exhibitions, graphic design, toys and film. Charles and Ray married in 1941 and moved to California where they pursued their furniture design work with molding plywood. During World War II they were commissioned by the US Navy to produce molded plywood splints, stretchers and experimental glider shells. Their molded plywood chair was called “the chair of the century” by the famous architecture critic Esther McCoy.
Keywords: Design; Meubelen